Neutronic experiment and analyses of a hybrid tritium breeding blanket mockup for CFETR. (October 2021) - Ma, Jimin; An, Li; He, Tie; Zhu, Tonghua; Guo, Haiping; Han, Zijie; Liu, Zhiyong; Bai, Jiangbo; Jiang, Li; Huang, Hongwen; Wang, Shaohua; Guo, Haibing; et al.
Highlights: A multi-layer mockup with uranium alloy disks and breeder pebble bed which represents real engineering design of HTBB has been setup. Several neutronic responses such as fission reaction rate, plutonium producction rate, activation reaction rate and tritium production rate have been measured. The C/E results show that calculations generally agree with experiments within 4% for tritium production rate. The experiment has provided validation to the HTBB design, calculation code and nuclear data used in the simulations. Abstract: A neutronic experiment has been performed using DT neutrons on a blanket mockup of the hybrid tritium breeding blanket (HTBB) at CAEP. As a backup blanket configuration for CFETR, HTBB design which uses uranium alloy, water coolant and ceramic breeder pebble bed has been proposed to obtain high tritium breeding ratio. The experiment has provided validation not only to the preliminary design of HTBB, but also to calculation code and nuclear data used in the simulations. Various neutron responses such as fission reaction rate, plutonium production rate, activation reaction rate and tritium production rate (TPR) have been measured. Numerical analyses were carried out with MCNP-4C code using ENDF/B-VII.1, TENDL-2017, IRDFF-v1.05 and FENDL3.1 nuclear data libraries. The comparisons between the calculation and experimental results show an agreement within about 10% for most of the measured quantities. The ratios of calculated to measured results (C/E) of tritium production rate are in 0.98–1.04 range which shows good agreement.